EFFECT OF USING CUE CARDS TO IMPROVE STUDENTS’ SKILLS IN WRITING DESCRIPTIVE TEXTS AT THE TENTH GRADE STUDENTS OF MA MA’ARIF 06 PASIR SAKTI - Siti Ulfa Khusniyah; Deri Sis Nanda (LINGUISTIKA, 2016)
The objective of this research is to find whether there is effect or not of using cue cards to improve students’ skills in writing descriptive texts for the tenth grade students of MA Ma’arif 06 Pasir Sakti. The research method was experimental class which conducted between the students of X IPS 1 and X IPS 2 as the subject.  The tenth grade of IPS 1 was taught using cue cards while the tenth grade of IPS 2 was taught without using cue cards. Based  on  the  result  of  data  analysis,  the  research  findings  are:  (1)  The cue cards is more  effective for teaching writing descriptive text than without using cue cards for tenth grade students of MA Ma’arif 06 Pasir Sakti;  (2)  The  students’ writing was improving after cue cards was applied. It can  be  concluded  that  cue cards is an effective media used to improve the writing skill of the tenth grade students of MA Ma’arif 06 Pasir Sakti.